Encroachers’ Perspective on Forest Encroachment in Kelantan, Malaysia - Masri, Nor Khafizah (2004)
There have been several studies conducted on the effects of deforestation, logging and shifting cultivation on Malaysia’s forest and yet little has been done on illegal forest encroachment aspects.Therefore, the objectives of this study were to assess socio-economic background of encroachers, their motivation to encroach as well as identifying factors influencing encroachment. This study was conducted in Kelantan, among one of the states in Peninsular Malaysia with the largest forest reserve and encroachment activities.Ninety-nine heads of households were selected through purposive sampling method. Data obtained were mainly analyzed through cross tabulations and frequencies tables; Kruskal Wallis test was performed to determine socio-economic differences among the territories while Multiple Disriminant Analysis (MDA) was conducted to identify variables which best predict encroachers’ choice of motivation to encroach. Results indicated that 63.6% of the encroachers fall in the lowest income range of RM250 - RM500 per month, lower than Malaysia's poverty Line threshold of RM510. Result on knowledge on land encroachment issues demonstrated most settlers are moderately aware of the issues pertaining to land encroachment. Nevertheless, they appear to have strong values and opinions that dismissed any wrongdoings in encroaching upon the forest which thus justify the encroachment behaviour. Kruskal Wallis test showed significant differences between territories in the aspects of distance of land from home, house value, and income level.The main motivational factor for encroachment as claimed by most of the settlers is poverty (40.4%).MDA analysis provided a weak model to predict on motivation to encroach hence signify on the needs to acknowledge on the influence of underlying factors towards encroachment behaviour such as individual perception and enforcement agencies’ limitation.Encroachment behaviour will be better understood if similar studies could be expanded to other states in Malaysia